Deep External Fluid Source Along the Gubbio Normal Fault (Italy): Implications for Slip Along the Altotiberina Active Low-Angle Normal Fault System - Riegel, Hannah; Casale, Gabriele; Mirabella, Francesco; Hyland, Ethan; Talegalli, Lorenzo (Frontiers in Earth Science, 2022)
Fluids play a critical role in fault slip, fault and damage zone development, and the distribution of seismicity in regional fault systems; however, determining the source of fluids within fault damage zones is complicated by superposition of fluid-related fabrics. Clumped isotopes applied to tectonic studies offer an opportunity to distinguish between fluid sources based on temperature and stable isotopic composition. Here we use the clumped isotope geothermometer and field observations and compare them with microstructural analysis to investigate the Gubbio normal-fault (GuF) core, a major SW-dipping epidetachment fault conjugate to the active Altotiberina low-angle normal fault in central Italy. Several distinct calcite vein sets reveal the incorporation of multiple generations of fluids during development of the damage zone. Clumped isotope results from these various precipitation phases record crystallization temperatures ranging from 87-154°C. These temperatures are broadly consistent with the presence of calcite deformation twin types II and III and are higher than estimates of regional peak burial temperatures. Additionally, stable isotope compositions within vein calcite are distinct from published isotopic values of the Apennine sedimentary succession, which constitutes the local bedrock. We propose that these observations suggest hydrothermal fluids migrated from depths greater than 6 km, which requires hydraulic connectivity along structural pathways between the shallow and deep crust, and fluid overpressures. These fluids reach the GuF via migration along the Altotiberina low-angle normal fault plane and they may be either of diagenetic or of deeper subduction origin. We suggest they possibly originated from the proximal retreating Apennine subduction system, implying that subduction processes exert spatial control on the distribution of fluid-assisted normal faulting and related seismicity which is consistent with the co-migration of closely coupled subduction and hinterland extension in the Apennines from Miocene to Present.